Prevalence and factors associated to cervical changes in units from the Single Health System - Indianara Carlotto Treco; Valquíria Kulig Vieira; Janaína Carla da Silva; Fernando Rodrigo Treco; Lirane Elize Defante Ferreto; Léia Carolina Lucio (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To estimate the prevalence and risk factors associated with cytopathological changes in the uterine cervix of women treated by the Unified Health System. Method: This is a cross-sectional study carried out with 350 women, between 14 and 79 years old who underwent pap smear tests in heath units in Francisco Beltrão, Paraná. Cervical cytopathological analyses and a questionnaire were applied to obtain socioeconomic information, as well as data on sexual behavior, gynecological aspects, and life habits. Chi-square test and logistic regression with p <0.05 were applied for statistical analysis. Results: The prevalence of cervical changes was 3.4% and the main categories found were low-grade cervical intraepithelial lesion, high-grade cervical intraepithelial lesion, and atypical cells of undetermined significance. From these, the first were present in 16.6% of women under 25 years old. The multivariate analysis pointed at associations between previous results of the cytopathology test (OR = 25.693), smoking (OR = 7.576), and oral contraceptives (OR = 5.265) and the outcome. Conclusion: Women with a history of previous cervical cytopathological abnormality, use of oral contraceptives, and smokers were more likely to have an abnormal result in the pap smear test.